Thalamic germinoma: A case report - Nithisha Thatikonda; Anand Pathak (Indian Journal of Child Health, 2021)
Germinomas involving non-midline structures such as thalamus and basal ganglia are relatively uncommon contributing up to 5–10% of all intracranial germ cell tumors. Here, we describe a case of thalamic germinoma in a 16-year-old boy who presented with recurrent episodes of headache and blurry vision for 2 months. Magnetic resonance imaging revealed heterogenous mass in the left thalamus with contrast enhancement causing mass effect and obstructive hydrocephalus. Total excision of the tumor was done by suboccipital craniotomy. Histopathology showed poorly differentiated round cells with vacuolated cytoplasm, round nuclei with prominent nucleoli which were separated by thin fibrovascular stroma infiltrated by lymphocytes. Immunohistochemistry showed diffuse immunoreactivity for placental alkaline phosphatase and octamer-binding transcription factor 3/4, and negative for glial fibrillary acidic protein, cluster of differentiation (CD)-45, and CD-30, confirming it to be a pure germinoma. With a combined approach of surgery, chemotherapy, and radiotherapy, these patients have better long-term survival rates.